Karakteristik ruas jalan nasional Suramadu Kabupaten Bangkalan STA 7+400 s.d STA 11+400 - yudhana, Galuh Catur; Hartatik, Nurani; Prasetyo, Yudi D. (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The Suramadu National Road is an important infrastructure that supports transportation access and the economy of the people of Bangkalan District and its surroundings. Road Functionality Tests are carried out to ensure that the road meets functional suitability standards that provide smoothness, safety and comfort for users. This research aims to identify the condition of functional fitness and assess the star rating score on the Suramadu National Road. Data collection was carried out based on Minister of Public Works Regulation Number 2 of 2022 concerning Procedures and Requirements for Road Functionality. The results of the analysis show that the 4 km Suramadu National Road section in Bangkalan Regency has quite good functional fitness, although there are several segments that do not meet standards, such as unofficial U-turns at several points and dead public road lighting. The condition of the road pavement was also found to be poor at several points. Overall, the Suramadu National Road received a Star Rating Score of 5.97 with a Star Rating category of 3, which shows that this road is suitable for operation in accordance with PUPR Ministerial Regulation No. 4 of 2023. According to Circular Letter Number 11/SE/Db/2024, this road is considered to meet the safety category. However, technical improvements are needed to achieve a safer road category with a Star Rating target of 4 and 5.